Pelatihan Guru Penggerak Bagi Guru Di SMP Negeri 2 Barru Sulawesi Selatan Sebagai Upaya Menyukseskan Program Merdeka Belajar - Atika Wijaya; Antari Ayuning Arsi; Ninuk Sholikhah Akhiroh (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The Freedom to Learn Program has various innovative programs in the education development. The old educational model is now transformed into a more flexible, explorative, and borderless. Thus, the readiness of the teacher is very important. The Mover Teacher Program is a challenge where teachers are required to be more creative and adaptive to change. However, this concept has not been fully understood by teachers outside Java Island. Therefore, the training of Mover Teachers needs to be carried out in SMP N 2 Barru South Sulawesi. This activity is carried out via online with expert as the initial stage and offline, mentoring as the final stage. With these two methods are expected to get more effective results to increase the capacity of teacher resources in Barru. The output of this dedication is that teachers can think innovatively and be ready to become mover teacher to success independent learning program.